Applying motivational interviewing techniques to increase faculty and staff motivation for change while decreasing resistance and fear of change. - Nadine A Hartig (Academic Chairpersons Conference Proceedings, 2015)
Motivational interviewing is a collaborative method to facilitate growth and change, particularly when someone is ambivalent about change. This session provides advanced skills for chairpersons to motivate faculty and staff, while avoiding resistance to change. Cases studies and skills practice are included.
Keywords: Motivation; mentoring; encouragement; change; resistance